Myeloablative and reduced-intensity conditioned allogeneic hematopoietic stem cell transplantation in myelofibrosis: a retrospective study by the chronic malignancies working party of the European Society for Blood and Marrow Transplantation - McLornan, Donal; Radujković, Aleksandar (Biology of blood and marrow transplantation, 2019)
This retrospective study by the European Society for Blood and Marrow Transplantation analyzed the outcome of 2224 patients with myelofibrosis (MF) who underwent allogeneic stem cell transplantation (allo-SCT) between 2000 and 2014; 781 (35%) underwent myeloablative conditioning (MAC) and 1443 (65%) reduced-intensity conditioning (RIC). Median patient age was 52.9 years (range, 18 to 74 years) and 57.5 years (range, 21 to 76 years) in the MAC and RIC cohorts, respectively. Donor type was similar: matched sibling donors (MAC, 317 [41%]; RIC, 552 [38%]) and unrelated donors (MAC, 464 [59%]; RIC, 891 [62%]). Median time to both neutrophil and platelet (>20×109/L) engraftment did not differ between cohorts. Rates of grade II to IV acute GVHD were 28% (MAC) and 31% (RIC; P = NS). Cumulative chronic GVHD rates (limited/extensive) were 22%/27% (MAC) and 19%/31% (RIC; P=.10). Cumulative incidences of nonrelapse mortality (NRM) at 1, 3, and 5 years were 25.5%, 32.2%, and 34.6% (MAC) and 26.3%, 32.8%, and 34.4% (RIC), respectively. There was a trend toward a higher relapse rate with RIC regimens compared with MAC (P=.08); rates at 1, 3, and 5 years were 10.9%, 17.2%, and 20.1% (MAC) and 14%, 19.7%, and 23.2% (RIC), respectively. No significant difference in 5-year probabilities of overall survival (OS) was noted: MAC (53.0%; 95% confidence interval [CI], 49.1% to 56.9%) and RIC (51.0%; 95% CI, 48.3% to 53.7%); P=.78. Regarding the composite end point of GVHD-free/relapse-free survival (GRFS), the unadjusted Kaplan-Meier estimate of 5-year GRFS was 32.4% (95% CI, 29.0% to 36.1%) in the MAC group and 26.1% (95% CI, 23.9% to 28.2%) in the RIC group (P=.001). In the MAC cohort, multivariable analysis confirmed worse OS and NRM with older age (>50 years), using an unrelated donor and a Karnofsky Performance Status of 80 or less. For the RIC cohort, worse OS and NRM were associated with age 60 to 70 years compared with younger recipients, use of a mismatched donor, and poor performance status. In conclusion, although similar OS rates existed for both cohorts overall, this study suggests that MAC should still be used for younger individuals suitable for such an approach due to a trend toward less relapse and an overall suggested advantage of improved GRFS, albeit this should be examined in a more homogeneous cohort. RIC allo-SCT still offers significant survival advantage in the older, fitter MF allograft patient, and optimization to reduce significant relapse and NRM rates is required.